Which feature is the main characteristic of a biographical text?
an argument presented from the author's perspective
text features
a particular focus on a person's life
figurative language
54 answers
a particular focus on a person's life
Which of the following categories would an article about the environmental impact of recycling most likely fall into?
informative nonfiction
memoir
biography
narrative nonfiction
informative nonfiction
memoir
biography
narrative nonfiction
informative nonfiction
In which subgenre would you be most likely to find an argumentative text?
autobiography
informative nonfiction
narrative nonfiction
biography
autobiography
informative nonfiction
narrative nonfiction
biography
informative nonfiction
What is the function of a nerve cell in a multicellular organism?
make and move protein
store and distribute oxygen
produce and manage movement
carry and transmit signals
make and move protein
store and distribute oxygen
produce and manage movement
carry and transmit signals
carry and transmit signals
How are red blood cells able to move through narrow vessels to carry oxygen throughout a multicellular organism?
They are small because their organelles are smaller than those of other cells.
They are long and thin with a tail-like end.
They are flexible because they lack a plasma membrane.
They are small because they lack a nucleus
They are small because their organelles are smaller than those of other cells.
They are long and thin with a tail-like end.
They are flexible because they lack a plasma membrane.
They are small because they lack a nucleus
They are small because they lack a nucleus
How do dendrites help the function of nerve cells?
They help the neuron block messages from the axon of another neuron.
They help the neuron receive messages from the axon of another neuron.
They help the neuron receive messages from the dendrites of another neuron.
They help the neuron block messages from the dendrites of another neuron.
They help the neuron block messages from the axon of another neuron.
They help the neuron receive messages from the axon of another neuron.
They help the neuron receive messages from the dendrites of another neuron.
They help the neuron block messages from the dendrites of another neuron.
They help the neuron receive messages from the axon of another neuron.
How might a red blood cell work with a neuron to support the function of a multicellular organism?
A neuron may signal when and where oxygen is needed.
A neuron may produce more red blood cells.
A red blood cell may produce more neurons.
A red blood cell may carry oxygen to the nucleus of a neuron.
A neuron may signal when and where oxygen is needed.
A neuron may produce more red blood cells.
A red blood cell may produce more neurons.
A red blood cell may carry oxygen to the nucleus of a neuron.
A neuron may signal when and where oxygen is needed.
How are red blood cells and neurons different?
Neurons contain DNA, but red blood cells do not.
Neurons are all the same size, but red blood cells are different sizes.
Neurons lack organelles, but red blood cells have organelles.
Neurons need oxygen, but red blood cells do not.
Neurons contain DNA, but red blood cells do not.
Neurons are all the same size, but red blood cells are different sizes.
Neurons lack organelles, but red blood cells have organelles.
Neurons need oxygen, but red blood cells do not.
Neurons lack organelles, but red blood cells have organelles.
What is 8 − 7 1/4
?(1 point)
?(1 point)
8 - 7 1/4 can be calculated as follows:
8 - 7 1/4 = 32/4 - 29/4
= (32 - 29)/4
= 3/4
Therefore, 8 - 7 1/4 equals 3/4.
8 - 7 1/4 = 32/4 - 29/4
= (32 - 29)/4
= 3/4
Therefore, 8 - 7 1/4 equals 3/4.
What is −4 5/11 − 2 4/11
?(1 point)
?(1 point)
To subtract −4 5/11 from −2 4/11, you can follow these steps:
Step 1:
Convert both mixed numbers to improper fractions.
-4 5/11 = -49/11
-2 4/11 = -26/11
Step 2:
Now, subtract the fractions:
(-49/11) - (-26/11)
= -49/11 + 26/11
= (-49 + 26)/11
= -23/11
Therefore, -4 5/11 - 2 4/11 equals -23/11.
Step 1:
Convert both mixed numbers to improper fractions.
-4 5/11 = -49/11
-2 4/11 = -26/11
Step 2:
Now, subtract the fractions:
(-49/11) - (-26/11)
= -49/11 + 26/11
= (-49 + 26)/11
= -23/11
Therefore, -4 5/11 - 2 4/11 equals -23/11.
23/11?
Apologies for the error. You are correct. The correct calculation is:
-4 5/11 - 2 4/11 = -49/11 - 26/11 = (-49 - 26)/11 = -75/11
Therefore, -4 5/11 - 2 4/11 equals -75/11. Thank you for catching that mistake.
-4 5/11 - 2 4/11 = -49/11 - 26/11 = (-49 - 26)/11 = -75/11
Therefore, -4 5/11 - 2 4/11 equals -75/11. Thank you for catching that mistake.
it's not 45/11 its 4 5/11 it not together
Apologies for the confusion. Let's recalculate it correctly:
-4 5/11 - 2 4/11 can be calculated as follows:
Step 1: Convert both mixed numbers to improper fractions.
-4 5/11 = -49/11
-2 4/11 = -30/11
Step 2: Subtract the fractions:
(-49/11) - (-30/11)
= -49/11 + 30/11
= (-49 + 30)/11
= -19/11
Therefore, -4 5/11 - 2 4/11 equals -19/11.
-4 5/11 - 2 4/11 can be calculated as follows:
Step 1: Convert both mixed numbers to improper fractions.
-4 5/11 = -49/11
-2 4/11 = -30/11
Step 2: Subtract the fractions:
(-49/11) - (-30/11)
= -49/11 + 30/11
= (-49 + 30)/11
= -19/11
Therefore, -4 5/11 - 2 4/11 equals -19/11.
it's 4 5/11 2 4/11 they both not together
Apologies for the misunderstanding. Let's recalculate with the correct expression:
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = 49/11
2 4/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11)
= (26 - 49)/11
= -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = 49/11
2 4/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11)
= (26 - 49)/11
= -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
that's wrong
Apologies for the repeated errors. Let's recalculate the expression correctly:
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = (4 * 11 + 5)/11 = 49/11
2 4/11 = (2 * 11 + 4)/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11) = (26 - 49)/11 = -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = (4 * 11 + 5)/11 = 49/11
2 4/11 = (2 * 11 + 4)/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11) = (26 - 49)/11 = -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
Your saying the same thing and it's not working do you mean 2 3/11?
Apologies for the repeated mistakes. You are correct, I made an error in my previous response. The correct calculation would be:
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = (4 * 11 + 5)/11 = 49/11
2 4/11 = (2 * 11 + 4)/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11) = (26 - 49)/11 = -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
To subtract 4 5/11 from 2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
4 5/11 = (4 * 11 + 5)/11 = 49/11
2 4/11 = (2 * 11 + 4)/11 = 26/11
Step 2: Subtract the fractions:
(26/11) - (49/11) = (26 - 49)/11 = -23/11
Therefore, 4 5/11 - 2 4/11 equals -23/11.
-4 5/11 from -2 4/11
To subtract -4 5/11 from -2 4/11, we can follow these steps:
Step 1: Convert both mixed numbers to improper fractions.
-4 5/11 = -(4 * 11 + 5)/11 = -49/11
-2 4/11 = -(2 * 11 + 4)/11 = -26/11
Step 2: Subtract the fractions:
(-26/11) - (-49/11) = (-26 + 49)/11 = 23/11
Therefore, -4 5/11 - (-2 4/11) equals 23/11.
Step 1: Convert both mixed numbers to improper fractions.
-4 5/11 = -(4 * 11 + 5)/11 = -49/11
-2 4/11 = -(2 * 11 + 4)/11 = -26/11
Step 2: Subtract the fractions:
(-26/11) - (-49/11) = (-26 + 49)/11 = 23/11
Therefore, -4 5/11 - (-2 4/11) equals 23/11.
What is 907.907−709.709
?(1 point)
?(1 point)
To find the difference between 907.907 and 709.709, we can subtract them:
907.907 - 709.709 = 198.198
Therefore, the answer is 198.198.
907.907 - 709.709 = 198.198
Therefore, the answer is 198.198.
What is 90.897−81.725
?(1 point)
?(1 point)
To find the difference between 90.897 and 81.725, we can subtract them:
90.897 - 81.725 = 9.172
Therefore, the answer is 9.172.
90.897 - 81.725 = 9.172
Therefore, the answer is 9.172.
What is 12 8/15 − 7 + 7/15 + 15? Simplify your answer.(1 point)
To simplify the expression 12 8/15 − 7 + 7/15 + 15, we can follow these steps:
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Rewrite the expression with the new fraction:
188/15 - 7 + 7/15 + 15
Step 3: Combine like terms:
(188/15 + 7/15) + 15 = 195/15 + 15
Step 4: Simplify the fraction by finding a common denominator:
(195 + 225)/15 = 420/15
Step 5: Simplify the fraction further by dividing both the numerator and denominator by their greatest common divisor (in this case, 15):
420/15 = (28 * 15)/(1 * 15) = 28/1
Therefore, 12 8/15 − 7 + 7/15 + 15 simplifies to 28/1 or simply 28.
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Rewrite the expression with the new fraction:
188/15 - 7 + 7/15 + 15
Step 3: Combine like terms:
(188/15 + 7/15) + 15 = 195/15 + 15
Step 4: Simplify the fraction by finding a common denominator:
(195 + 225)/15 = 420/15
Step 5: Simplify the fraction further by dividing both the numerator and denominator by their greatest common divisor (in this case, 15):
420/15 = (28 * 15)/(1 * 15) = 28/1
Therefore, 12 8/15 − 7 + 7/15 + 15 simplifies to 28/1 or simply 28.
What is 12 8/15 − 7 + 7/15 + 15? Simplify your answer
21
21
20 15/15
20 Start Fraction 15 over 15 End Fraction
41 15/15
41 Start Fraction 15 over 15 End Fraction
35
35
21
21
20 15/15
20 Start Fraction 15 over 15 End Fraction
41 15/15
41 Start Fraction 15 over 15 End Fraction
35
35
To simplify the expression 12 8/15 - 7 + 7/15 + 15, we can follow these steps:
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Add the fractions and whole numbers separately:
188/15 - 7 + 7/15 + 15
Step 3: Combine the fractions:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 = 13
Step 5: Add the final whole number:
13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Add the fractions and whole numbers separately:
188/15 - 7 + 7/15 + 15
Step 3: Combine the fractions:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 = 13
Step 5: Add the final whole number:
13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
thats not an answer
Apologies for the mistake. Let's reevaluate the expression correctly:
To simplify 12 8/15 - 7 + 7/15 + 15, let's perform the calculations step by step:
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Rewrite the expression with the fraction:
188/15 - 7 + 7/15 + 15
Step 3: Combine like terms:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 can be simplified by dividing the numerator and denominator by 15:
195/15 = 13/1
Step 5: Add the final whole number:
13/1 + 15 = 13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
To simplify 12 8/15 - 7 + 7/15 + 15, let's perform the calculations step by step:
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Rewrite the expression with the fraction:
188/15 - 7 + 7/15 + 15
Step 3: Combine like terms:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 can be simplified by dividing the numerator and denominator by 15:
195/15 = 13/1
Step 5: Add the final whole number:
13/1 + 15 = 13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
the answers are 21
21
20 15/5
20 Start Fraction 15 over 15 End Fraction
41 15/15
41 Start Fraction 15 over 15 End Fraction
35
35
21
20 15/5
20 Start Fraction 15 over 15 End Fraction
41 15/15
41 Start Fraction 15 over 15 End Fraction
35
35
Apologies for the confusion. Let's go through the calculations again:
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Simplify the expression:
188/15 - 7 + 7/15 + 15
Step 3: Combine the fractions:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 can be simplified by dividing the numerator and denominator by their greatest common divisor, which is 15:
195/15 = (13 * 15)/(1 * 15) = 13/1 = 13
Step 5: Add the final whole number:
13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
Step 1: Convert the mixed number 12 8/15 to an improper fraction:
12 8/15 = (12 * 15 + 8)/15 = 188/15
Step 2: Simplify the expression:
188/15 - 7 + 7/15 + 15
Step 3: Combine the fractions:
(188/15 + 7/15) = 195/15
Step 4: Simplify the fraction:
195/15 can be simplified by dividing the numerator and denominator by their greatest common divisor, which is 15:
195/15 = (13 * 15)/(1 * 15) = 13/1 = 13
Step 5: Add the final whole number:
13 + 15 = 28
Therefore, the simplified answer to 12 8/15 - 7 + 7/15 + 15 is 28.
What should you do if a place value is missing a number?(1 point)
Responses
Nothing.
Nothing.
Add a zero.
Add a zero.
Remove the last digit(s) in the number that has the additional place values.
Remove the last digit(s) in the number that has the additional place values.
Subtract without it.
Responses
Nothing.
Nothing.
Add a zero.
Add a zero.
Remove the last digit(s) in the number that has the additional place values.
Remove the last digit(s) in the number that has the additional place values.
Subtract without it.
Add a zero.
What is −18.1−5?(1 point)
Responses
−23.1
negative 23.1
−13.1
negative 13.1
13.1
13.1
23.1
23.1
Responses
−23.1
negative 23.1
−13.1
negative 13.1
13.1
13.1
23.1
23.1
-18.1 - 5 = -23.1
Therefore, the answer is -23.1.
Therefore, the answer is -23.1.
189.987−30.87
To subtract 30.87 from 189.987, we can follow these steps:
189.987 - 30.87 = 159.117
Therefore, 189.987 - 30.87 equals 159.117.
189.987 - 30.87 = 159.117
Therefore, 189.987 - 30.87 equals 159.117.
Mark had a balance of −$11
in his checking account. The bank charged a $25 fee. What is the balance in the account?(1 point)
The balance in the account is $
in his checking account. The bank charged a $25 fee. What is the balance in the account?(1 point)
The balance in the account is $
To find the balance in Mark's account after the bank charged a $25 fee, we can subtract the fee from the initial balance:
Balance after fee = Initial balance - Fee
Balance after fee = -$11 - $25
Balance after fee = -$36
Therefore, the balance in Mark's account after the fee is -$36.
Balance after fee = Initial balance - Fee
Balance after fee = -$11 - $25
Balance after fee = -$36
Therefore, the balance in Mark's account after the fee is -$36.
The water level of a river is below normal levels. Its water level is at 1 1/2
meters below sea level. During the summer, the river drops another 2 1/3
meters below sea level. What is the water level at the end of summer? Remember, the elevation is below sea level. Account for this in your answer.(1 point)
The water level is
meters below sea level.
meters below sea level. During the summer, the river drops another 2 1/3
meters below sea level. What is the water level at the end of summer? Remember, the elevation is below sea level. Account for this in your answer.(1 point)
The water level is
meters below sea level.
To determine the water level at the end of summer, we need to subtract the additional drop of 2 1/3 meters from the initial level of 1 1/2 meters below sea level.
Step 1: Convert the mixed numbers to improper fractions:
1 1/2 = (1 * 2 + 1)/2 = 3/2
2 1/3 = (2 * 3 + 1)/3 = 7/3
Step 2: Subtract 7/3 from 3/2:
3/2 - 7/3 = (9/6) - (14/6) = -5/6
Therefore, at the end of summer, the water level is 5/6 meters below sea level.
Step 1: Convert the mixed numbers to improper fractions:
1 1/2 = (1 * 2 + 1)/2 = 3/2
2 1/3 = (2 * 3 + 1)/3 = 7/3
Step 2: Subtract 7/3 from 3/2:
3/2 - 7/3 = (9/6) - (14/6) = -5/6
Therefore, at the end of summer, the water level is 5/6 meters below sea level.
bruh